2003
DOI: 10.1002/chin.200337174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1‐β‐D‐(5‐Deoxy‐5‐iodoarabinofuranosyl)‐2‐nitroimidazole (β‐IAZA): A Novel Marker of Tissue Hypoxia.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…These results suggested that further investigation on nitrobenzoimidazole and nitrotriazole as tumor hypoxia markers was needed [40]. (11) and fell in the optimum range of an ideal hypoxic marker (0.01~0.1). In vivo distribution was performed in mammary tumor-bearing rats using a gamma camera and associated computer.…”
Section: Metronidazolesmentioning
confidence: 85%
See 1 more Smart Citation
“…These results suggested that further investigation on nitrobenzoimidazole and nitrotriazole as tumor hypoxia markers was needed [40]. (11) and fell in the optimum range of an ideal hypoxic marker (0.01~0.1). In vivo distribution was performed in mammary tumor-bearing rats using a gamma camera and associated computer.…”
Section: Metronidazolesmentioning
confidence: 85%
“…(4)). The -IAZA was synthesized via an unconventional route in satisfactory yield with a change of configuration at the C-2'-position, which may be used as a novel marker of tissue hypoxia [11]. Radioiodinated IAZA analogues are evaluated using microPET and animals.…”
Section: Radioiodinated 2-nitroimidazolesmentioning
confidence: 99%
“…[3,7,12] b-AZA (5) was prepared via an unconventional route starting from 1-b-D-(ribofuranosyl)-2-nitroimidazole (AZR), with a change of configuration at the C-2'-position. [6] Trace amounts of b-AZA were reported as a sideproduct in the a-AZA synthesis from 1-a-bromo-2,3,5-tri-O-benzoylarabinofuranose, but no chemical characterization was provided. [12] In the present study, both a-AZA and b-AZA were obtained by reacting 2-nitroimidazole with a mixture of a-and b-1-O-acetyl-2,3,5-tri-O-benzoyl-D-arabinofuranose (2) in the presence of stannic chloride, followed by deprotection in the presence of ammonia/methanol (Scheme 1).…”
Section: Discussionmentioning
confidence: 98%
“…The melting points, 1 H and 13 C NMR spectra for 5 and 6 were identical to those reported previously. [6,7] ABBREVIATIONS AZA 1-D-arabinofuranosyl-2-nitroimidazole IAZA 1-D-(5-deoxy-5-iodoarabinofuranosyl)-2-nitroimidazole DDQ 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone AZR 1-b-D-(ribofuranosyl)-2-nitroimidazole Hg(CN) 2 mercuric cyanide…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation